PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP IT AD DURRAH : Pembelajaran berbasis masalah, kemampuan menulis, teks deskripsi, siswa - Nursamsia Rambe; Riris Nurkholidah Rambe (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
This study aims to determini the effect of problem-based learning models on the ability to write descriptive texts of seventh-grade students at SMP IT Ad Durrah Marelan. This study uses a quantitative method with a quasi-experimental design. The research sample consists of two classes: an experimental class that receives treatment and a control class that does not receive treatment. Data collection techniques use multiple-choice tests in the form of student work in writing descriptive texts. Data analysis techniques start with normality tests, homogeneity tests, and then proceed with hypothesis testing. The results of this study show that the data obtained from post-test and pre-test were analyzed using the T-test from two parties, which gave results that students who were given treatment in the learning process using problem-based learning models experienced more improvement compared to those who were not given PBL learning strategies. This can be seen from the calculation results, where the t-count value is 0.95, while the t table value is 2.0089. This proves that the hypothesis test is accepted and there is a difference in writing descriptive texts between students who were given problem lased learning models and those who were not is bold.